Models of hepatoprotective activity assessment - Delgado Montemayor, Cecilia; Cordero Pérez, Paula; Salazar Aranda, Ricardo; Waksman Minsky, Noemí Herminia (UANL. Facultad de Medicina, 2015)
Liver diseases are a major health problem worldwide, making it necessary to develop new molecules that help counteract or prevent such diseases. On account of this fact, investigations aiming to obtain natural and/or synthetic compounds possessing hepatoprotective activity have been undertaken. The development of new drugs consists of a variety of steps, ranging from the discovery of the pharmacological effects in cellular and animal models, to finally demonstrate their efficacy and safety in humans. Different models for assessment of the hepatoprotective activity in vitro, ex vivo and in vivo can be found in medical literature. The purpose of this review is to show the features, main advantages and disadvantages of each of the models, the hepatotoxic agents most commonly used (CCl4, acetaminophen, ethanol, dgalactosamine, t-BuOOH, thioacetamide) as well as the biochemical parameters useful to assess liver damage in the different models.